2022
DOI: 10.2147/dddt.s378976
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Geniposide on Glucose and Lipid Metabolism: A Review

Abstract: Geniposide is a naturally sourced active ingredient that has diverse pharmacological effects and great potential in improving or treating different kinds of diseases. In recent years, more and more studies have confirmed that geniposide can improve glucose and lipid metabolism disorder, which is an increasingly prevalent health problem causing various metabolic diseases globally. Our review aims to summarize basic information on the pharmacological effects of geniposide on glucolipid metabolism. Geniposide inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…GEN is a natural compound that has been found to have therapeutic benefits and treat a variety of diseases, including osteoporosis [ 50 , 51 ]. GEN can up-regulate the expression of GLP-1R and ABCA1 in CHO-treated osteoblasts and promote CHO efflux from osteoblasts, suggesting that GEN might be the potential candidate for managing high-CHO-induced osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…GEN is a natural compound that has been found to have therapeutic benefits and treat a variety of diseases, including osteoporosis [ 50 , 51 ]. GEN can up-regulate the expression of GLP-1R and ABCA1 in CHO-treated osteoblasts and promote CHO efflux from osteoblasts, suggesting that GEN might be the potential candidate for managing high-CHO-induced osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that geniposide could significantly upregulate the protein levels of Glc NAc T-Ⅳ, a glycosyltransferase, but had no significant effect on the expression of clathrin [ 35 ]. Some studies found that gardeniside could stimulate the glycogen synthesis in the mice with a high-fat diet and a streptozotocin injection [ 36 ]. Therefore, in this research, the result of geniposide was effective in vivo but not in vitro, which also complemented the mechanism that the primary target of the geniposide participating in the treatment of T2DM was not α-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…During wine processing, the C-7 position in the iridoids chemical structure could be readily cleaved, the C-4 position could be easily substituted with hydroxyl groups, and the formation of glycosides by the disaccharide group becomes favorable under high temperatures and enzymatic action. Previous studies have reported that iridoids have the potential to enhance insulin resistance and ameliorate lipid metabolism disorders in vivo ( Wang et al, 2020a ; Gao and Feng 2022 ). Additionally, they exhibited blood glucose-lowering effects and effectiveness in combating diabetic complications ( Kong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%